2018
DOI: 10.1111/joic.12555
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between pre‐procedural plaque morphology and patterns of in‐stent neointimal hyperplasia at 1‐year follow‐up in patients treated with new‐generation drug‐eluting stents: An optical coherence tomography based analysis

Abstract: Instruction: Several factors affect the in-stent intimal healing process after drugeluting stents (DESs) implantation. We hope to investigate the influence of plaque characteristics on subsequent heterogeneous neointimal hyperplasia (NIH) using optical coherence tomography (OCT). Methods:The study population consisted 217 patients with single-vessel de novo lesions who underwent both pre-procedural OCT scan and 12-month follow-up OCT examination. NIH is defined as at least five consecutive cross-sectional imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 46 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…MBs are mostly found in the middle segment of the LAD, and the result was similar to our finding. Unlike CAG, OCT could not only identify MB but also the plaque character 20 . Xu and his colleges have reported that stable fibrous plaques, but no lipid or other types of plaque, were found in the MB segment of all 12 patients under the guidance of OCT 21 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…MBs are mostly found in the middle segment of the LAD, and the result was similar to our finding. Unlike CAG, OCT could not only identify MB but also the plaque character 20 . Xu and his colleges have reported that stable fibrous plaques, but no lipid or other types of plaque, were found in the MB segment of all 12 patients under the guidance of OCT 21 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the etiology of this phenomenon is not clear. OCT is a novel imaging technology based on light, which can be used to study tissues in vivo 20 . Its ultra-high resolution is about 10 µm, which can display the anatomical structure of the coronary artery and provide a high-quality coronary artery image 20 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent clinical trials have demonstrated that rivaroxaban reduces mortality and cardiovascular events, including stent thrombosis, in patients with regarding neointimal growth and indicated different time courses for vascular response between DAPT and CR or AR treatments. Since the heterogeneous pattern is thought to be linked to poor long-term prognoses [40][41][42] , a lower proportion of heterogeneous patterns in AR and CR might indicate a beneficial effect. The high proportion of layered patterns in the AR and CR groups at 1 month might reflect a clearer boundary between SMCs with contractile and synthetic features.…”
Section: Advance Publication Journal Of Atherosclerosis and Thrombosismentioning
confidence: 99%